The Effect of the Labor Force Participation Rate (LFPR) and Population on Economic Growth in North Sumatra - Era Widia Br Sinaga; Annisah Saajidah; Elisa Clara Saragih; Melani Manginar Sirait; Relli Anisma Hutabalian; Nasrullah Hidayat (Jurnal Ekonomi Balance, 2025)
This study investigates the effect of the Labor Force Participation Rate (LFPR) and population size on economic growth in North Sumatra Province during the 2018–2023 period. Economic growth remains a crucial indicator of regional development performance, particularly in provinces experiencing demographic dynamics and labor market fluctuations. Using a quantitative approach, this study employs multiple linear regression analysis based on secondary data obtained from the Central Bureau of Statistics (BPS) and the North Sumatra Manpower Office. Prior to estimation, classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity were conducted to ensure model robustness. The empirical results reveal that LFPR has a positive and statistically significant effect on economic growth, indicating that higher labor market participation enhances regional production capacity and output. Population size also shows a positive and significant influence, suggesting that population growth can stimulate economic activity through expanded labor supply and consumption demand when properly managed. Simultaneously, LFPR and population significantly affect economic growth, as confirmed by the F-test results. The coefficient of determination (R²) of 91.84% indicates that the two independent variables explain a substantial proportion of variations in economic growth in North Sumatra. These findings highlight the strategic role of labor force engagement and demographic management in fostering sustainable regional economic growth. Policy implications emphasize the importance of job creation, workforce skill development, and human capital investment to maximize the benefits of demographic potential and support inclusive economic development in North Sumatra Province.